Global public goods, global regulation and development of transition economies – some remarks - Olszewski, Leon (Wydawnictwo Uniwersytetu Wrocławskiego, 2009)
The process of economic globalization has been precipitated over the last three decades. The global public good has gained increasing attention. The global problems we face today require international or global solutions. The new global economic conditions affect the way that states operate today in a global world. In this note, we consider the consequences of the global rules for the development of transition economies. We show the danger of imposing on emerging economies the same global and regional measures regarding environmental and financial issues.
Keywords: globalne regulacje; dobra publiczne; globalne dobra publiczne